Pengaruh Pengetahuan Kebencanaan Penduduk di Wilayah Resiko Tinggi Tanah Longsor terhadap Upaya Pengembangan Program Desa Tangguh Bencana - Aneng Yuningsih; Kurniawan Kurniawan; Asep Setiadi (STIKes Karsa Husada Garut, 2017)
Villagers in the village are actors and beneficiaries of the direct impact of the disaster. From several types of natural disasters, landslides are one of the most frequent natural disasters in Indonesia. Community-based disaster risk reduction is a process of disaster risk management involving communities actively in reviewing, analyzing, handling, monitoring and evaluating disaster risks. The purpose of this study is to examine the effect of disaster population knowledge on high risk areas of landslide on the efforts of developing a robust village disaster program. The method used in this literature review is to collect and analyze research articles and journals (national and international) related to population disaster knowledge in the high risk areas of landslides and the development of rural disaster-prone villages. Articles obtained from electronic journals from Science direct, Proquest, Google Scholar, SAGE Jurnals, PubMed Central International, JSTOR, Scopus etc. The inclusion criteria of this literature review is an article published between 2008-2017. From the study of this literature, obtained 10 research articles that analyze the influence of knowledge disaster people in high-risk landslide areas to the efforts of the development of village disaster resilient program significantly. Based on the literature review shows there is a positive influence. This means that the higher the population's knowledge of disaster, the higher the chances in developing the Tangguh Disaster Rural Program. Thus the development of a resilient village program can be an effort to increase the role of community-based organizations in promoting disaster preparedness at the community level.